1807 Ky. Acts 1 - (:unkn) unknown (My University, 1807)
An Act to Amend an act titled "An Act Concerning the Militia," ch. 1§ 3: Imposed a fine of up to fifty cents on each non commissioned officer and private appearing on parade without a gun after being duly notified.
Keywords: ARMED FORCES